Dârüssaâde Ağası Moralı Beşir Ağa (?-1752) - Elvan, Derya (My University, 2025)
Moralı Beşir Ağa’nın biyografisinin ele alındığı bu çalışma, giriş ve üç bölümden müteşekkildir. Girişte çalışmamızın temelini oluşturan kaynak türleri elealınmıştır. Moralı Beşir Ağa’nın kariyerinde yükselişi, siyasete müdahalesi ve nüfuzundan oluşmaktadır. İkinci bölüm, Beşir Ağa’yı idama götüren sebepler ve nihayetinde azli ve idamı, hizbinin merkez ve taşradaki faaliyetleri, ticari ağları, hizbin tasfiyesi ve elde etmiş oldukları gelirlerin hazineye aktarılmasını kapsamaktadır. Çalışmamızın son bölümünde Moralı Beşir Ağa’nın şahsi özellikleri, sanat ve spordaki başarısı ve kurmuş olduğu vakıflar ele alınmıştır.

This study, which examines the biography of Morean Beşir Ağa consists of an introduction and three chapters. In the introduction, the types of sources that form the basis of our in study for this thesis were discussed. The first chapter covers Morean Beşir Ağa's rise in career, his intervention in politics, his influence, and the reasons that led to his execution, and ultimately his dismissal and execution. The second chapter covers the activities of the Beşir Ağa’s faction in the center and the provinces, its commercial networks, disbanding the faction and the transfer of the total income they obtained to the state treasury. The last part of our thesis covers the personal characteristics of Morean Beşir Ağa, his success in arts and sports, and the foundations he established are discussed.
Keywords: 18. Yüzyıl; 18th Century; Ağası Moralı Beşir Ağa (?-1752); Biography; Biyografi; Chief Eunuch; Dârüssaâde; Faction; Hizip; Memurlar ve çalışanlar; Moralı Beşir Ağa; Morean Beşir Ağa; Officials and employees; Topkapı Palace; Topkapı Sarayı; Turkey; Türkiye